1985
DOI: 10.1523/jneurosci.05-04-01090.1985
|View full text |Cite
|
Sign up to set email alerts
|

Antibody against nerve growth factor-inducible large external (NILE) glycoprotein labels nerve fiber tracts in the developing rat nervous system

Abstract: The NILE (nerve growth factor-inducible large external) glycoprotein is a 230,000-dalton molecule found on the surface of PC12 cells. immunologically cross-reactive glycoproteins in the molecular weight range of 215,000 to 230,000 have been found on many types of neurons in culture. Using immunohistochemical methods, we have shown that NILErelated glycoproteins are present in neuronal fiber tracts of the developing rat brain. Antibody against the NILE glycoprotein specifically labels processes that appear iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 32 publications
3
86
1
Order By: Relevance
“…In a previous study (16), we found that a construct called L1lacZ containing an 18-kb segment of the mouse L1 gene produced a neurally restricted pattern of ␤-galactosidase expression. This pattern was in accord with previous immunohistochemical and in situ hybridization studies that localized the protein and mRNA expression for L1 during early neural development (12,20,25,26). L1lacZ⌬N, a construct similar to L1lacZ but lacking the NRSE normally found in the second intron of the L1 gene, showed ectopic L1 promoter activity in several nonneural tissues between days 8.5 and 13.5 of embryonic development (16).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a previous study (16), we found that a construct called L1lacZ containing an 18-kb segment of the mouse L1 gene produced a neurally restricted pattern of ␤-galactosidase expression. This pattern was in accord with previous immunohistochemical and in situ hybridization studies that localized the protein and mRNA expression for L1 during early neural development (12,20,25,26). L1lacZ⌬N, a construct similar to L1lacZ but lacking the NRSE normally found in the second intron of the L1 gene, showed ectopic L1 promoter activity in several nonneural tissues between days 8.5 and 13.5 of embryonic development (16).…”
Section: Discussionsupporting
confidence: 90%
“…Although the L1 cell adhesion molecule is first expressed during the differentiation of postmitotic neurons from neuroepithelial precursors (20), the most abundant expression of L1 mRNA and protein occurs during the period of postnatal development (21). At this time, there is an extensive outgrowth of neurons and formation of synaptic connections.…”
mentioning
confidence: 99%
“…Furthermore, several independent in vitro experiments, including antibody perturbation studies and direct neurite outgrowth assays using these proteins, either immobilized on cell culture dishes or expressed by transfection in cell lines, have revealed compelling evidence that these Ig/FNIII-like proteins participate in axonal growth processes (Stallcup and Beasley, 1985;Hoffman et al, 1986;Fischer et al, 1986;Chang et al, 1987;Rathjen et al, 1987a,b;Lagenaur and Lemmon, 1987;Ruegg et al, 1989;Chang et al, 1990;Furley et al, 1990;Kadmon et al, 1990;Stoeckli et al, 1991;Gennarini et al, 1991).…”
Section: Structural Features Of Ig/fniii-like Proteins Concentrated Omentioning
confidence: 99%
“…L1 plays a role in axonal outgrowth, fasciculation, and guidance during spinal cord development (Stallcup et al, 1985;Jessell, 1988;Stoeckli and Landmesser, 1995;Orlino et al, 2000;Tran and Phelps, 2000;Akopians et al, 2003) through homophilic and various heterophilic binding partners such as integrins (αVβ3 and α5β1) and the fibroblast growth factor receptor (Kamiguchi and Lemmon, 1997). L1 interacts with TAG-1 and DM-1 GRASP to promote neurite growth, whereas binding with *Please address correspondence to: Patricia E. Phelps, Ph.D., Dept.…”
mentioning
confidence: 99%